Potensi Pemanfaatan Serum Mir 122-5p Sebagai Biomarker Dalam Deteksi Dini Infark Miokard Akut Pada Pasien Lanjut Usia - Siregar, Muhammad Abi Ghoffari; Hidayat, Fariz; Rayhansyah, Vito (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2024)
Acute myocardial infarction is the first manifestation of CAD which is the leading cause of death worldwide. The increasing incidence is often associated with increasing age where eldery are mostly affected with this disease. Although there are several biomarkers such as troponin I and T in detecting the risk of developing AMI, it has been found that populations over 70 years have elevated troponin I levels and increased troponin T levels in non-AMI cases. Because of that, a specific biomarker that can specifically detect AMI is needed. This literature review is aimed to discuss the possibility by using miR-122-5p serum for specific biomarker in detecting AMI in eldery population. The literature search was conducted based on journal searching related to the topic such as, PubMed, Science Direct, and Google Scholar. Based on the literature research we have done and our topic, we have obtained the results as follows. Pathogenesis of AMI, the underlying mechanism of miR-122-5p in association with AMI, the specificity of miR-122-5p for AMI, and the comparison of miR-122-5p with other AMI biomarkers. From the pathogenesis of AMI, we have obtained the basis of the disease, the underlying mechanism explains the potential relation to AMI and the detection, through the specificity we can see how it may be effective as a biomarker, and the comparison may reveal it’s potential and how it compares to other biomarkers.